Thinking About a Diet?. Issue 1 (January 2015) - Morin, Karen H.
<x xml:space="preserve">Abstract</x> Which diet works best: low carbohydrate or low fat? Our nutrition expert, Dr. Morin, provides the latest information to help guide women who may be asking about weight loss dieting.